Textual Criticism of the Hebrew Bible - Tov, Emanuel (Brill Book Archive Part 1, ISBN: 9789004472495, 2005)
Customers in North America who wish to purchase this publication, please contact Augsburg Fortress Press. First published in 1992, Emanuel Tov's Textual Criticism of the Hebrew Bible has rapidly established itself as the authoritative reference work for all those engaged in the study of the text of the Hebrew Bible. This thoroughly revised second edition will be welcomed by students and scholars alike. A wide range of readers will find this book accessible and indispensable. Emanuel Tov offers extensive descriptions of the major witnesses to the text of the Hebrew Bible-the Hebrew texts from Qumran, the Septuagint, the Masoretic Text-as well as the Aramaic Targumim, the Syriac translations, the Vulgate, and others. Special attention is given to the exegetical aspects of the textual transmission, literary issues, and the problem of the original shape of the biblical text. Praise for the First Edition: "Emanuel Tov is preeminent in the world in the field of Septuagint studies. This is a solid and durable work which, given its technical character, is written in a readable way." Frank Moore Cross, Harvard University "Nowhere else can you find such a thorough presentation of how the Bible was transmitted in Second Temple times. This excellently written handbook represents a major step forward for biblical studies." Lawrence Schiffman, New York University "History will surely regard Emanuel Tov's monumental work as the definitive discussion of textual criticism of this generation. A 'must-have' for any serious scholar of the Bible!" Sidnie A. White, University of Nebraska "The basic reference work on the textual criticism of the Hebrew Bible for at least the next decade. This is a magisterial work which is badly needed and masterfully done." Journal for the Study of Judaism "This book will soon be viewed as a classic of biblical studies." Ralph W. Klein, Journal of Religion "Replete with examples, tables, plates, lucid definitions and explanations, as well as extensive bibliographies, the volume brings together a wealth of information not previously so accessible and makes the theory and practice of textual criticism easily understandable and visually clear." Judith E. Sanderson, Seattle University.